Perception and Prospective Analysis of Artificial Intelligence on Human Capital and its Impact on Human Resources in The Industrial Revolution Era 4.0 - Btari Purwaamijaya Mariska; Yogi Prasetyo; Fadhilah Fadhilah (Institute of Computer Science (IOCS), 2021)
In the current global Industry 4.0 era, competent and highly competitive human resources are an absolute requirement for increasingly fierce global competition, to deal with this the Indonesian government has implemented policies to deal with Indonesia's Industry 4.0. One of them is carried out by the Ministry of Research and Technology, over the last four years, around 100 new study programs have been opened to produce human resources who are ready to face challenges in Indonesia's Industry 4.0. The depiction of the global era of Industry 4.0 can be described as follows: automation and robotics are considered as muscles, AR / VR, cameras and other sensors are considered as senses, data and connectivity are considered as a central nervous system. But the real brain behind it is Artificial Intelligence (AI). AI is a science in the field of computer science that studies the creation of computer systems with the ability to have human-like intelligence. People who have AI skills are highly targeted nowadays. Demand for artificial intelligence capabilities in the focused area of ​​machine learning has increased sharply in the UK. Research is needed with a comprehensive qualitative approach, and exploration of the needs anticipated by universities to become centers of excellence and contribute to the real world by producing human resources to be able to work and win the competition in the global business industry, both as practitioners and academics. The results of the study are useful for improvement and aim to evaluate the strategies that have been implemented previously based on the results of research related to perceptions and prospective analysis of artificial intelligence to produce the human resources needed in Industry 4.0 in Indonesia.